Mediastinal drainage combined with upper mediastinal re-tunneling vs. mediastinal drainage alone in McKeown esophagectomy of esophageal cancer: a retrospective study - Dai, Lei; Tan, Xiang; Chen, Mingwu; Peng, Huajian; Wang, Yongyong (Frontiers in Surgery, 2024)
BackgroundAlthough mediastinal drainage may lower the risk of anastomotic leakage, the incident rate of anastomotic leakage is still high. The current study aimed to compare the effects of mediastinal drainage combined with upper mediastinal re-tunneling with mediastinal drainage only on anastomotic leakage after McKeown esophagectomy for esophageal cancer.MethodsFrom October 2018 to March 2021, 52 patients diagnosed as esophageal carcinoma were included in the study. 21 patients received mediastinal drainage combined with upper mediastinal re-tunneling (re-tunneling group) and 31 received mediastinal drainage only (standard group) after McKeown esophagectomy. The incidence rate of anastomotic leakage, mediastinal infection, chylothorax, thoracic infection, the peak value of leukocyte count and the mortality related to anastomotic leakage were compared between the two groups.ResultsOne (4.8%) patient in the re-tunneling group developed anastomotic leakage, and no patient experienced mediastinal infection or thoracic infection. Four (12.9%) patients in the standard group developed anastomotic leakage, and all these patients experienced mediastinal infection and thoracic infection (p < 0.05). The drainage volumes of patients in the re-tunneling group and the standard group were (170 ± 60) ml and (155 ± 45) ml, respectively, with no significant difference between the two groups (p > 0.05). The peak values of leukocyte count and temperature in the re-tunneling group were (14.28 ± 1.12) × 109/L and (38.6 ± 1.1) °C, both lower than that of the standard group[ (16.48 ± 1.15) × 109/L and (38.9 ± 1.2) °C, respectively]. But the difference was not statistically significant (p > 0.05). No anastomotic leakage related death occurred in both groups.ConclusionMediastinal drainage combined with upper mediastinal re-tunneling after McKeown esophagectomy for esophageal cancer may decrease the risk of anastomotic leakage, mediastinal and thoracic infection, reduce the inflammatory response of patients, but did not increase the mortality related to anastomotic leakage.Trial registrationThe study was retrospectively registered.